Perlindungan Hukum Terhadap Masyarakat yang Terpapar Limbah B3 - Abidin, Zainal; Akli, Zul; J, Johari (Jurnal Ilmu Hukum Reusam, 2020)
This research examines the legal protection of people who are victims of the B3 madical waste. This research is a qualitative research with literature study. The main sources in this research are written sources in the form of books, research results, and laws which related to the issue. The results showed that the law provides protection to people who are exposed to the B3 madical waste, both criminal and civil law. When a dispute happening between the community and the company, the solution can be done in two ways, litigation and non-litigation. Settlement of environmental disputes through channels outside the court according to Article 85 paragraph (3) can only be done by using the services of a mediator and / or arbitrator to help resolve the dispute. Active community participation can be carried out by referring to Article 86 of the PPLH Law by establishing a free and impartial environmental dispute resolution institution facilitated by the government and local governments.